2022
DOI: 10.31234/osf.io/uphkt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of High Versus Low Cognitive Load on the Development of Nociceptive Hypersensitivity: The Roles of Sympathetic Arousal, Sex, and Pain-Related Fear

Abstract: According to limited-capacity theories, the processing of nociceptive stimuli may be reduced when less attentional resources are available, which may diminish the development of secondary hypersensitivity, i.e. the increased sensitivity to mechanical pinprick stimuli applied in the uninjured area. In this study, we used Low Frequency Stimulation (LFS) to examine the contributions of cognitive load, its modulation by sex, and sympathetic arousal to the development of secondary mechanical hypersensitivity. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…Although the effect size is small, our findings are in line with studies that have shown that other top-down factors can modulate SH [22,32,45,57,67]. Importantly however, other recent studies that have used similar electrical stimulation protocols, have found either modest or no modulation of SH [4,18,48,65]. This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg.…”
Section: Effects Of Social Support On the Development Of Shsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the effect size is small, our findings are in line with studies that have shown that other top-down factors can modulate SH [22,32,45,57,67]. Importantly however, other recent studies that have used similar electrical stimulation protocols, have found either modest or no modulation of SH [4,18,48,65]. This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg.…”
Section: Effects Of Social Support On the Development Of Shsupporting
confidence: 87%
“…However, it is not clear that being distracted after the stimulation can impact the development of SH. Most studies that have attempted to modulate SH via attentional effects have focused on the stimulation period [22,48,64]. Any distraction caused by the presence of the partner during the stimulation, may have been minimized since providing ratings for the MFS stimulation would have kept participants' attention focused on the stimulation.…”
Section: Effects Of Social Support On the Development Of Shmentioning
confidence: 99%
“…Although the effect size is small, our findings are in line with studies that have shown that other top-down factors can modulate SH [22,32,45,57,67]. Importantly however, other recent studies that have used similar electrical stimulation protocols, have found either modest or no modulation of SH [4,18,48,65]. This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg.…”
Section: Effects Of Social Support On the Development Of Shsupporting
confidence: 87%
“…Previous studies using a secondary hyperalgesia paradigm, another indirect measure of central sensitization (Woolf, 2011), yielded conflicting results. While some authors argue that difficult tasks (such as n-back) (Torta et al, 2020) reduce the development of this phenomenon, others find no effect of working memory/cognitive load nor of spatial attention to the location, on the development of secondary hyperalgesia (Della Porta et al, 2022;Meyers et al, 2022Meyers et al, , 2023. Although both phenomena are related to central sensitization, TSSP is a phenomenon independent of secondary hyperalgesia and with distinct underlying mechanisms (Woolf, 2011), and may therefore be affected differently by attention/cognitive load.…”
Section: Discussionmentioning
confidence: 99%